(untitled) (International Journal of Engineering and Computer Science, 2018)
Thousand of persons are being killed as a cause of earthquake. The disaster in the Dhaka City may claim thousands of lives due to Earthquake. It is said if survivors are found and rescued earlier the numbers of victims will be lower. There is no end to the number of lives lost as the result of such disasters as landslides, collapsed tunnels and avalanches. The microwave life detection system is developed for the search and rescue of victims trapped under the rubble of collapsed building during the earthquake or other disasters. In this project, an ultra-sensitive compact portable microwave life-detection device is introduced and implemented with promising results. By utilizing Doppler effect-based systems, vital signs such as heartbeats and breathing can be detected and can be used for finding survivors under earthquake rubble, injured soldiers on battlefields and as lie detection device. This device is tested in both simulated and realistic situations, and it can accurately detect crucial signs of life through highly dense construction materials of about 1.5m thick and standard density materials of about 10m while operating at 1.15GHz center frequency.